CMS data processing workflows during an extended cosmic ray run - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Adam, W; Arnold, B; Bergauer, H; Bergauer, T; Dragicevic, M; Eichberger, M; Erö, J; Friedl, M; Frühwirth, R; et al. (2010)
The CMS Collaboration conducted a month-long data taking exercise, the Cosmic Run At Four Tesla, during October-November 2008, with the goal of commissioning the experiment for extended operation. With all installed detector systems participating, CMS recorded 270 million cosmic ray events with the solenoid at a magnetic field strength of 3.8 T. This paper describes the data flow from the detector through the various online and offline computing systems, as well as the workflows used for recording the data, for aligning and calibrating the detector, and for analysis of the data. © 2010 IOP Publishing Ltd and SISSA.